Analysing income distribution changes: Anonymous versus panel income approaches - Robert Duval-Hernández; Gary S. Fields; George H. Jakubson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We reconcile, both theoretically and empirically, changes in inequality with panel income changes over periods of economic growth and decline. We also explore what factors account for the trends of short-run inequality and of inequality in individual average earnings. Finally, we explore what factors account for the equalization brought about by economic mobility. Using panel earnings data from Mexico we find that earnings changes are convergent, irrespective of whether inequality rises or falls. This is caused by a small fraction of individuals experiencing large and convergent earnings changes. The equalization that earnings changes bring over a year is mainly driven by changes in the employment and sector of workers.
Keywords: J31; D63; 330; income inequality; economic mobility